2017
DOI: 10.1007/s00198-017-4222-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of high-dose vitamin D3 supplementation on bone mineral density in subjects with prediabetes

Abstract: Vitamin D supplementation alone may be beneficial in males with prediabetes, but confirmatory studies are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…Further, there was no significant effect of vitamin D treatment on BMD, which is in line with a recent meta-analysis [6]. In contrast, Larsen et al [15] found a small, but significant positive effect of five years of vitamin D supplementation at a dose of 20,000 IU weekly on femoral neck BMD in males with prediabetes. In this context, it should also be noted that subgroup analyses of RCTs suggested that improvements of BMD by vitamin D supplementation may be observed only in individuals with 25(OH)D levels ≤30 nmol/L with no significant effect at higher 25(OH)D levels [16,21].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Further, there was no significant effect of vitamin D treatment on BMD, which is in line with a recent meta-analysis [6]. In contrast, Larsen et al [15] found a small, but significant positive effect of five years of vitamin D supplementation at a dose of 20,000 IU weekly on femoral neck BMD in males with prediabetes. In this context, it should also be noted that subgroup analyses of RCTs suggested that improvements of BMD by vitamin D supplementation may be observed only in individuals with 25(OH)D levels ≤30 nmol/L with no significant effect at higher 25(OH)D levels [16,21].…”
Section: Discussionsupporting
confidence: 79%
“…Biobanking of remaining blood samples was performed by freezing and storing at −80 °C until analysis. Serum levels of 25(OH)D and TT were additionally measured by well-adjusted Isotope-Dilution Liquid Chromatography Tandem Mass Spectrometry (ID-LC-MS/MS) methods in 2018 [15,16]. Only 25(OH)D levels measured by ID-LC-MS/MS are used for all statistical analyses in the manuscript.…”
Section: Methodsmentioning
confidence: 99%
“…Among the 11 RCTs, 3 (27%) used daily dosing with vitamin D,42,43,47 but dosing regimens in the 8 other RCTs varied from weekly (1 [9%]), 40 monthly (1 [9%]), 46 quarterly (2 [18%]), 39,41 every 4 months (2 [18%]),44,48 to annually (2 [18%]) 45,49. Moreover, only 2 of 11 RCTs (18%) assessed the effects of equivalent daily doses of vitamin D greater than 2000 IU 40,46. Two RCTs45,49 assessed very high annual doses of vitamin D, which appeared to increase the risk of fractures and falls among those allocated to the vitamin D group.…”
mentioning
confidence: 99%
“…Consistent with a meta‐analysis of RCTs that showed a significantly inferior effect of higher‐dose vitamin D supplementation on aBMD in the lumbar spine compared with lower‐dose vitamin D supplementation, Mendelian randomization analyses have found a possible inverse relation of vitamin D status with skeletal health . Consequently, the possibility of a causal positive association between serum 25(OH)D levels and aBMD would be almost ruled out by these two key analyses to assess causality, though the indirect effects of high‐dose vitamin D supplements in RCTs could be detected in the hip or tibia . Accordingly, the positive linear correlation between serum 25(OH)D levels at 12 months and change in aBMD in the lumbar spine can be interpreted as a result of the involvement of individual life and health status including physical activity outdoors because the wide variability in serum 25(OH)D levels after supplementation with vitamin D suggests that serum 25(OH)D levels at 12 months resulted not only from vitamin D supplements, but also from other factors such as vitamin D synthesis in the skin following sunlight exposure.…”
mentioning
confidence: 88%